Ethnicity Guaylla (now Huaylas) - Espinoza Soriano, Waldermar (2013)
Both in the Age of the Incas as in earlier times, the Andean —Costa, Sierra and Ceja de Selva, was inhabited by a large number of chiefdoms and kingdoms, which is scientifically preferred ethnic name. Indeed, one of the notorious and significant was formed, developed and died in Huaylas. Their economic, social and political depended on farming activities and, secondly, livestock. Socially and politically, was divided into two halves: Anan and Lurin, curacas governed by strict hierarchical order according to decimal. Classes knew and worshiped many gods.